Cropping Pattern, Intensity and Diversity in Dhaka Region (Bangladesh Rice Journal, 2018)
Sustainable crop production in Bangladesh through improvement of cropping intensity and crop diversity in rice based cropping system is regarded as increasingly important in national issues. Planning of agricultural development largely depends on the authentic, reliable and comprehensive statistics of the existing cropping patterns, cropping intensity and crop diversity of a particular area, which will provide guideline to our policy makers, researchers, extensionists and development workers. The study was conducted over all 46 upazilas of Dhaka agricultural region in 2015 using pretested semi-structured questionnaire with a view to document the existing cropping patterns, cropping intensity and crop diversity in the region. From the present study, it was observed that about 48.27% net cropped area (NCA) is covered by exclusive rice cropping systems whereas deep water rice occupied about 16.57% of the regional NCA. The most dominant cropping pattern Boro−Fallow−T. Aman alone occupied about 22.59% of net cropped area (NCA) with its distribution over 32 upazilas out of 46. The second largest area was covered by single Boro cropping pattern, which was spread over 44 upazilas. Total number of cropping patterns was observed 164. The highest number of cropping pattern was identified 35 in Tangail sadar and Dhamrai upazila of Dhaka district and the lowest was seven in Bandar of Narayanganj and Palash of Narsingdi district. The lowest crop diversity index (CDI) was reported as 0.70 in Dhamrai followed by 0.72 in Monohardi of Narsingdi. The highest value of CDI was observed as 0.97 in Tangail sadar followed by 0.95 in Dhamrai of Dhaka and Bhuanpur of Tangail. The range of cropping intensity value was recorded 124-239%. The maximum CDI was observed in Saturia upazila of Manikganj district and minimum in Sreenagar upazila of Munsiganj district. The CDI value for Dhaka region was calculated 0.94 and the average cropping intensity at regional level was 191%.Bangladesh Rice j. 2017, 21(2): 123-141